Love for a laugh - Tan, Yanbing (Brill, 2023)
After the strikingly beautiful Peony Pavilion, how could one write about love and the ideal of emotional authenticity (qing) in the chuanqi genre? This book presents a group of creative dramatists who confronted this challenge by giving the romantic theme of chuanqi their unique comic twists. This book demonstrates how their comic articulations bring the qing ideal down to the mundane world of family obligations, political ambitions, commercial interests, and gender frustrations. By highlighting the crucial but understudied role that the comic plays, this book enriches our understanding of the intellectual depth and critical scope of the chuanqi genre
http://dx.doi.org/10.1163/9789004548237
Keywords: Asian history; Asiatische Geschichte; HISTORY / Asia / General; HISTORY / Middle East / General; LITERARY CRITICISM / Drama; Literary studies: plays & playwrights; Literaturwissenschaft: Dramen und Dramatiker